2007
DOI: 10.1016/j.ijgo.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and metabolic features of polycystic ovary syndrome

Abstract: Menstrual abnormality and polycystic ovaries were the main clinical manifestations in this cohort of Chinese women with PCOS. The prevalence of hyperandrogenism, obesity, and insulin resistance was lower in this cohort than in women from other races with the same condition. Ethnic differences needs to be considered when studying the clinical and metabolic features of women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 31 publications
2
37
2
1
Order By: Relevance
“…Another factor, which contributed to the lower prevalence of MetS in our population of PCOS patients, was BMI. The BMI values in the Chinese PCOS patients were usually lower and central obesity less popular than other ethnicities (30,(33)(34)(35), whereas central obesity is one of the main contributors to developing the MetS. In our study, mean BMI was also lower than those in America, Germany, Australia, India, and Thailand.…”
Section: Discussioncontrasting
confidence: 42%
“…Another factor, which contributed to the lower prevalence of MetS in our population of PCOS patients, was BMI. The BMI values in the Chinese PCOS patients were usually lower and central obesity less popular than other ethnicities (30,(33)(34)(35), whereas central obesity is one of the main contributors to developing the MetS. In our study, mean BMI was also lower than those in America, Germany, Australia, India, and Thailand.…”
Section: Discussioncontrasting
confidence: 42%
“…Menstrual irregularity was observed in 83% of our patients while study conducted by Vrunda Dhagat reported 65% in the same [9]. The frequency of hirsutism was comparable to that noted in Chinese women (35%), while acne was present only in 13% patients, as compared to 45% in the Chinese study group [10]. Apparently, 57% of the married patients were fertile even though only 25% reported worldwide [11].…”
Section: Discussionsupporting
confidence: 56%
“…Its prevalence ranges from 4%-12% in general population of women in the world of reproductive age. [22][23][24][25][26][27][28] Although there are no systemic studies from India, the observations by endocrinologists, gynaecologists, dermatologists, etc. show a significant rise in number of females with PCOS nevertheless prevalence of PCOS in Indian adolescents estimated at 9.13%.…”
Section: Introductionmentioning
confidence: 99%